2003
DOI: 10.1083/jcb.200212064
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle repair by adult human mesenchymal stem cells from synovial membrane

Abstract: We have demonstrated previously that adult human synovial membrane-derived mesenchymal stem cells (hSM-MSCs) have myogenic potential in vitro (De Bari, C., F. Dell'Accio, P. Tylzanowski, and F.P. Luyten. 2001. Arthritis Rheum. 44:1928–1942). In the present study, we have characterized their myogenic differentiation in a nude mouse model of skeletal muscle regeneration and provide proof of principle of their potential use for muscle repair in the mdx mouse model of Duchenne muscular dystrophy. When implanted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
289
1
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(308 citation statements)
references
References 45 publications
10
289
1
7
Order By: Relevance
“…Similar contribution to the satellite cell pool has been demonstrated in injured mouse muscles for muscle SP cells, 21 muscle-derived floating populations, 42 CD133 ϩ cells, 24 and synovial membrane-derived mesenchymal stem cells. 75 However, this is the first time that this behavioral feature is described in highly damaged muscles such as those in GRMD dogs. In addition to their participation on fiber regeneration and satellite cell formation, we observed that MuStem cells intriguingly gave rise to interstitial cells.…”
Section: Discussionmentioning
confidence: 80%
“…Similar contribution to the satellite cell pool has been demonstrated in injured mouse muscles for muscle SP cells, 21 muscle-derived floating populations, 42 CD133 ϩ cells, 24 and synovial membrane-derived mesenchymal stem cells. 75 However, this is the first time that this behavioral feature is described in highly damaged muscles such as those in GRMD dogs. In addition to their participation on fiber regeneration and satellite cell formation, we observed that MuStem cells intriguingly gave rise to interstitial cells.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, synovium-derived MSCs had great differentiation potential for adipogenesis and osteogenesis as well as chondrogenesis. De Bari and colleagues previously reported that synovium-derived MSCs had myogenic potential both in vitro and in vivo (27), suggesting the high multipotentiality of synovium-derived MSCs.…”
mentioning
confidence: 98%
“…This further supported the multipotent potential of CFU-Fs. Similar cells have been isolated from different mesenchymal tissues, including synovia (De Bari et al, 2003), tendons (Salingcarnboriboon et al, 2003), skeletal muscles (Bosch et al, 2000) and adipose tissue (Zuk et al, 2001Erickson et al, 2002), including the fat pad of the knee joint (Dragoo et al, 2003). These MSCs were also found in peripheral blood (Kuznetsov et al, 2001); however, their frequency is probably extremely low or variable (Zvaifler et al, 2000) and they are characterized by different cell surface markers (Table 1).…”
Section: Bone Marrow-derived Stromal Stem Cellsmentioning
confidence: 83%